Synthesis of Mesoporous Silica Particles by Polymerization Induced Colloid Aggregation and Its Application for High-Performance Liquid Chromatography - Zhao, B.B.; Wang, F.Y.; Li, T. (Asian Journal of Chemistry, 2015)
Micrometer-sized mesoporous silica particles have been synthesized by a modified polymerization induced colloid aggregation method. Silica particles with particle size in the range of 2-5 μm could be obtained by controlling the reaction conditions. The obtained silica particles were characterized by scanning electron microscopy (SEM), N2 physisorption technique and inductively coupled plasma emission spectroscopy (ICP-AES). The C18-modified silica particles were explored as stationary phase in reversed phase liquid chromatography and its chromatographic characteristics for separation of some small molecules have been studied.